THE COURAGE OF THE ANCESTORS IS AN EXAMPLE FOR THE YOUTH:HE MADE A WORTHY CONTRIBUTION TO THE VICTORY IN THE SECOND WORLD WAR ABOUT OUR COMPATRIOTS - Lieutenant Colonel Rajabov Mirzo Jurakulovich (Web of Journals Publishing, 2023)
This article examines the experience of the Second World War and discusses the great contribution of our compatriots, who protected their chests for the Fatherland, to the victory of the Soviet Union in the Second World War, as well as the worthy contribution of young men and women who worked tirelessly day and night and delivered goods to the front.
Keywords: World history, World War II, National Rifle Brigade, front, military academy.